Pengaruh Latihan Wall Drills terhadap Kemampuan Tendangan Naeryo Chagi - Sugar Wanto; Azizil Fikri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine whether the effect of wall drills training on the ability to kick naeryo chagipada extracurricular Tae Kwon Do High School river candle. The method used in this study was a pure experimental method due to randomization, the experimental group (treatment) and the control group. Population in this study is all students who take extracurricular Tae Kwon Do, amounting to 20 people, each student 10 people as an experimental class and 10 people as a control class. Samples are given wall drills for 4 weeks with a frequency of 3 times a week. After 4 weeks there is an effect of wall drills training on the ability of naeryo chagi kicks in the Tae Kwon Do sport, which is an average posttest score of 34.2 with a difference of 4.2, and an average posttest result of 32.1 with a difference of 2 , 1. tcount 7.20> t table 1.73. Conclusion, that the wall drills exercise affects the ability of naeryo chagi kicks in Ta Kwon Do's extracurricular activities Keywords: Wall Drills, Kick, Naeryo Changi